2010
DOI: 10.1093/nar/gkq174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of the full APOBEC3 mRNA repertoire in lymphocytes and tissues: implications for HIV-1 restriction

Abstract: The human APOBEC3 proteins are DNA cytidine deaminases that impede the replication of many different transposons and viruses. The genes that encode APOBEC3A, APOBEC3B, APOBEC3C, APOBEC3D, APOBEC3F, APOBEC3G and APOBEC3H were generated through relatively recent recombination events. The resulting high degree of inter-relatedness has complicated the development of specific quantitative PCR assays for these genes despite considerable interest in understanding their expression profiles. Here, we describe a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
439
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(480 citation statements)
references
References 60 publications
38
439
1
2
Order By: Relevance
“…mRNA Quantification-A3A mRNA was quantified by quantitative RT-PCR relative to the stable housekeeping transcript, TBP, using highly specific primers, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA Quantification-A3A mRNA was quantified by quantitative RT-PCR relative to the stable housekeeping transcript, TBP, using highly specific primers, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…These professional phagocytic cells are stationed throughout the body to perform immune surveillance and thus come into contact with a variety of foreign molecules, including DNA. APOBEC3A (A3A) 5 is part of the APOBEC3 family of DNA cytosine deaminases, which in humans is composed of seven members: A, B, C, D, F, G, and H. A3A is the most active of these deaminases (2), but its expression is limited to myeloid lineage cells and therefore likely has a specialized function in these cells (3)(4)(5)(6). A3A is strongly induced by type I interferon (10 -1000-fold) (4, 6 -8) and is also induced by other immunostimulatory molecules such as cytosolic DNA (6).…”
mentioning
confidence: 99%
“…CC mutations indicate editing by A3G because A3G is the only A3 protein with a CC preference. In contrast, one cannot definitively attribute mutations that arise in a TC context in vivo to a particular human A3 protein because all six human A3 proteins besides A3G display a preference for editing at TC motifs, and some primary human cell types express more than one A3 protein (47,48). Moreover, little is known about in vivo regulation of A3 proteins, which could affect the ability of A3 proteins to interact with and edit viral DNA.…”
Section: A3mentioning
confidence: 99%
“…Interferons (IFNs) and hypoxia induce C > U RNA editing in an additive manner in monocytes, increasing the RNA editing levels to above 80% for several tested genes. Gene expression, transfection, knockdown, site-directed mutagenesis studies and in vitro analysis by purified protein showed that APOBEC3A (A3A), a cytidine deaminase which is structurally related to APOBEC1 and expressed primarily in myeloid cells including monocytes and macrophages, 7 catalyzes this RNA editing. 6 Thus, A3A is a novel C > U RNA editing enzyme.…”
mentioning
confidence: 99%